GRAMMATICAL ERROR IN WRITING RECOUNT TEXTS - Sulistika Ningsih; Herlina; Santi Mayasari (Universitas PGRI Palembang, 2024)
TThe purpose of this study was to analyze the many kinds of grammatical errors that fall under four different categories—omission, addition, misorder, and distortion—as well as the reasons behind them when producing recount texts. The study employed a descriptive-qualitative research design. The participants were the 24 eighth-grade students from SMP Negeri 45 Palembang who were enrolled for the 2023–2024 academic year. The researcher employed questionnaires and writing tests as instruments to gather data, which was subsequently analyzed. The results revealed that 221 errors total—65 (29,4%) in the Omission category, 41 (18,6%) in the Addition category, 16 (7,2%) in the Misorder category, and 99 (44,8%) in the Misformation category—were committed by the students. When composing recall texts, students most frequently committed mistakes in the Misformation category. The questionnaire's results showed that students were not only interested in producing recount texts, but also, perhaps because of their limited vocabulary, they were not quite aware of how to apply grammatical structures in their writing.